Low amount of Au nanoparticles deposited ZnO nanorods heterojunction photocatalysts for efficient degradation of p-nitrophenol - Bai, Lei; Mei, Jinxiang (Journal of sol-gel science and technology, 2020)
By chemical precipitation of Au nanoparticles on the ZnO nanorods, the heterostructures were successfully obtained. The structures were investigated by several methods and it was revealed that with the increase of the Au precursor, the size of Au nanoparticles was increased and the interaction between Au nanoparticle and ZnO nanorod was also confirmed. The performance of the photodegradation of p -nitrophenol suggested that the activity was related with the amount of Au nanoparticles in Au/ZnO heterostructure to a great extent. It was suggested that by taking advantage of the one dimension ZnO nanorods with the effect of aspect ratio and surface defects as well as the local surface plasma resonance adsorption of Au nanoparticles, the heterostructures demonstrated an ideal activity under visible light for the disposal of low concentration of organic pollutants, suggesting a potential application in environmental remediation. By taking advantage of one dimension ZnO nanorod with the effect of aspect ratio and surface defects as well as the local surface plasma resonance adsorption of Au nanoparticles, the Au nanoparticles/ZnO nanorods heterostructures were synthesized and demonstrated an ideal activity under visible light for the degradation of low concentration of organic pollutants. Highlights The Au nanoparticle/ZnO nanorod was synthesized. A large increase of photoactivity was observed due to the synergistic effect of Au. The Au/ZnO demonstrated a potential application in environmental remediation.